A Design of Early Fire Detection System In Tobacco Oven Based on Internet of Things (Case Study: East Landah Praya Village) - Chairuman Fadhilah; Ariyan Zubaidi; Ahmad Zafrullah Mardiansyah (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2023)
A tobacco oven is a building measuring 4.5 x 4.5 meters that are used to bake freshly harvested tobacco leaves and can accommodate up to 5-7 shelves. The oven building is equipped with 2 bottom vents and 2 top vents that function as temperature and humidity regulators by opening or closing the vents. Tobacco oven techniques in Lombok itself can not be said to be safe, it is proven that fires in tobacco ovens often occur lately. One of the causes of tobacco oven fires is due to the presence of tobacco leaves that fall into the furnace so that the fire quickly grabs the tobacco in a semi-dry state, in addition, due to the lack of use of safety equipment above the ignition furnace, the fallen dried tobacco leaves can immediately burn. Based on these problems, research entitled